2020
DOI: 10.3390/ijerph17062100
|View full text |Cite
|
Sign up to set email alerts
|

Bean Preferences Vary by Acculturation Level among Latinas and by Ethnicity with Non-Hispanic White Women

Abstract: With high levels of protein, fiber, folate, iron and other micronutrients, the Dietary Guidelines for Americans recommends eating beans for optimal nutrition. Low-income women are at greater risk of nutrition-related health disparities. Use of beans may change among Hispanic women (Latinas) during acculturation, but few studies exist that describe specific preferences of this important traditional food. Preserving or promoting beans in the diets of all low-income women could improve dietary quality. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
2
7
1
Order By: Relevance
“…As with the college students in this study, other research supports that most people have a positive attitude toward beans/pulses, like the taste of them, and purchase both dry and canned [18,28,[36][37][38][39]. Black beans, lentils, pinto beans, and chickpeas were the most common types of pulses cooked, which is similar to pulse popularity found in other studies in North America [11,18,19,28,36].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…As with the college students in this study, other research supports that most people have a positive attitude toward beans/pulses, like the taste of them, and purchase both dry and canned [18,28,[36][37][38][39]. Black beans, lentils, pinto beans, and chickpeas were the most common types of pulses cooked, which is similar to pulse popularity found in other studies in North America [11,18,19,28,36].…”
Section: Discussionsupporting
confidence: 84%
“…Similar research conducted with participants of an older age and greater ethnic/racial diversity than the Midwestern US college students showed higher pulse consumption rates. Eighty percent of Hispanic and Non-Hispanic White women in Iowa [ 28 , 42 ], 89% of Hispanic and Non-Hispanic White women in Arizona [ 36 ], and 79% of low-income White, Black, and Hispanic men in Arizona [ 37 ] reported consuming beans at least 2–3 times per month. Just over half of adults ≥65 years old in a Canadian study reported consuming beans on a daily or weekly basis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Latino foods, such as beans, corn tortillas, lean meats, and fresh fruits and vegetables, are considered healthy and recommended by the 2015-2020 Dietary Guidelines for Americans (DGA) [11]. The inclusion of these foods in an adapted NEMS-S may more accurately describe Latino markets and food environments [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%